SAFETY EVALUATION, IN VITRO ANTIDIABETIC STUDY AND GC-MS PROFILING OF A FORMULATED POLYHERBAL SYRUP - Dauda, Joseph Abiodun; Khan, Emmanuel M .; Abdullahi, Shehu; Jacob, A. David; Okpanachi, Baba C.; Ogohi, D. Agah; Ejukwa, E. Ekpe; Zaccheaus, Oyiza R. (FUDMA Journal of Sciences, 2026)
Diabetes mellitus remains a major metabolic disorder requiring safer and affordable therapeutic alternatives. This study evaluated the safety profile, in vitro antidiabetic activity, and phytochemical composition of a formulated polyherbal syrup(PHS)prepared from Vernonia amygdalina, Moringa oleifera, Zingiber officinale, Allium cepa, and Allium sativum. Aqueous extracts of onion, garlic, and ginger were obtained by decoction of 20 g powdered samples in 100 mL distilled water at 40 °C for 3 h, while fresh leaves of Moringa oleifera and Vernonia amygdalina were extracted by manual juice expression and filtration. The extracts were combined with honey to produce the polyherbal syrup. Acute toxicity evaluation in albino rats using oral doses of 1000–16000 mg/kg body weight revealed no mortality or visible signs of toxicity, indicating an LD₅₀ greater than 16000 mg/kg. Sub-acute toxicity studies conducted at doses of 25–400 mg/kg also showed no adverse behavioural or physiological changes. In vitro antidiabetic assays revealed that PHS is concentration-dependent. The PHS exhibited IC₅₀ values(µg/mL)of 8.88 for glucose uptake, 2.55 for α-amylase inhibition, and 3.50 for α-glucosidase inhibition, compared with the standard drug acarbose which showed IC₅₀ values of 3.55, 1.89, and 3.39 µg/mL respectively. Although the standard drug showed slightly higher potency, the PHS demonstrated comparable α-glucosidase inhibitory activity. GC–MS profiling revealed numerous bioactive phytochemicals including 2,3-dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one, 5-hydroxymethylfurfural, thymine, n-hexadecanoic acid, and octadec-9-enoic acid. The combined presence of these compounds suggests possible synergistic pharmacological interactions responsible for the observed antidiabetic effects. These findings indicate that the formulated polyherbal syrup is safe and possesses promising antidiabetic potential.